2017
DOI: 10.3390/ijms18030607
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus and Iron Deficiencies Influences Rice Shoot Growth in an Oxygen Dependent Manner: Insight from Upland and Lowland Rice

Abstract: Abstract:Rice is the main staple crop for one-third of the world population. To maximize yields, large quantities and constant input of fertilizers containing essential nutrients such as phosphorus (P) and iron (Fe) are added. Rice can germinate in both aerobic and anaerobic conditions, but the crosstalk between oxygen (O 2 ) and nutrients such as P and Fe on plant growth remains obscure. The aim of this work was to test whether such interactions exist, and, if so, if they are conserved between up-and lowland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…It has been previously demonstrated that the shoot and root biomass of rice varieties are affected by the availability of Pi and/or Fe concentration in the medium [ 24 ]. Whether also an interaction among Si, Pi, and/or Fe homeostasis controls rice growth is unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously demonstrated that the shoot and root biomass of rice varieties are affected by the availability of Pi and/or Fe concentration in the medium [ 24 ]. Whether also an interaction among Si, Pi, and/or Fe homeostasis controls rice growth is unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study showed that the majority of transcript changes observed in the absence of Fe (−Fe growth conditions) were repressed if Pi was also absent (−Fe−Pi). At phenotypic level, it has been shown that Pi and Fe interact in an antagonistic manner to modulate rice growth [ 22 , 23 , 24 ]. For instance, rice growth is severely affected by Fe deficiency and can be inverted by simultaneous Fe and P deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed the presence of an interaction between the mineral nutrients and oxygen to modulates rice growth capacity (Saenchai et al, 2016;Mongon et al, 2017). Availability of mineral nutrients for plants growth and development is important (Rouached et al, 2010;Bouain et al, 2014) to ensure a better growth and a high yield.…”
Section: Introductionmentioning
confidence: 99%
“…191 192 Gene expression data is increasing with the use of transcriptomic technologies, requiring the development 193 of methods for their efficient analysis. Combination with functional genomics approaches these 194 computational tools can help to gain new insight on the molecular mechanisms of complex phenomenon 195 such as the regulation of ions homeostasis in plants (Mongon et al, 2017;Rouached and Rhee, 2017). In 196 this context, we developed and used an algorithm, TransDetect, to identify regulators (TFs) and to build 197 a GRNs that control the expression of a Pi transporter, PHO1;H3, in response to -Zn conditions.…”
Section: Ice1 Regulates Pi Accumulation Under Zn Deficiency In a Myb1mentioning
confidence: 99%